Оюуны довтолгооны аргыг англи хэлний сургалтад ашиглах нь: Using Brainstorming in English Language Teaching - G., Tserendavaa; G., Baigalmaa (Mongolian Journal of Foreign Languages and Cultures, 2023)
Brainstorming is considered one of the most useful techniques of learner-centered approach, which is used in decision-making, problem-solving and team-working process. The paper focuses on some issues of using brainstorming and its application in English language teaching. The method is more productive as a whole-class activity. It helps learners to think more freely and creatively than more controlled activities. This paper describes some findings of the study and observations that have been conducted by the authors.